2015
DOI: 10.1039/c5cs00343a
|View full text |Cite
|
Sign up to set email alerts
|

Core–shell nanoparticles: synthesis and applications in catalysis and electrocatalysis

Abstract: Core-shell nanoparticles (CSNs) are a class of nanostructured materials that have recently received increased attention owing to their interesting properties and broad range of applications in catalysis, biology, materials chemistry and sensors. By rationally tuning the cores as well as the shells of such materials, a range of core-shell nanoparticles can be produced with tailorable properties that can play important roles in various catalytic processes and offer sustainable solutions to current energy problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
507
0
31

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 980 publications
(539 citation statements)
references
References 459 publications
(702 reference statements)
1
507
0
31
Order By: Relevance
“…Confinement via encapsulation as one possible strategy for catalyst design also works for electrochemical systems:126 Galeano et al 123. reported that AuPt@C yolk–shell materials showed strongly enhanced stability in repeated fuel cell start–stop cycles.…”
Section: Rational Design Of Catalysts and New Reactor Conceptsmentioning
confidence: 99%
“…Confinement via encapsulation as one possible strategy for catalyst design also works for electrochemical systems:126 Galeano et al 123. reported that AuPt@C yolk–shell materials showed strongly enhanced stability in repeated fuel cell start–stop cycles.…”
Section: Rational Design Of Catalysts and New Reactor Conceptsmentioning
confidence: 99%
“…C. Wang et al [ 279 ] reported a study on the effect of the electrode pulverization upon cycling. They demonstrated that Ni/ bottom-up-synthesized graphene yolk-shell [ 280 ] nanohybrids (i.e., composites constituted by Ni core particles which behave like a movable yolk inside the graphene hollow shell) exhibited enhanced capacity and rate capability compared to their coreshell [ 281 ] counterparts (i.e., composites constructed with a fi xed Ni core and an outer shell of graphene). The authors claimed that the improvements arose from lowered activation barriers for lithiation/delithiation and improved availability of ions at the interface, leading to a stable long-term cycling (i.e., more than 1700 cycles for an applied current of 5 A g −1 in the potential range 0.005-3 V) with a reversible capacity of about 490 mAh g −1 .…”
mentioning
confidence: 99%
“…A number of different methods have been previously reported for the preparation of bimetallic Au/Fe alloy nanoparticles, 13−15,20−26 core−shell or dumbbell nanoparticles, 27,28 with protocols including thermal decomposition, 15,23 pulsed laser deposition, 29,30 microemulsion techniques, 16,31 thermal vaporization, 32,33 laser-assisted synthesis in solution, 13,20 and aqueous reduction by borohydride derivates. 14 Chemical reduction of metal ions by sodium borohydrides has previously been used to prepare nanocrystalline magnetic materials, nanoalloys, and amorphous metals.…”
Section: ■ Introductionmentioning
confidence: 99%